An integrated approach identifying seasonal variation in allergenic grass pollen in southern Australia - Josh Boyte; Sarah M. Sherson; Lachlan Tegart; Nithya Fernandopulle; Hee Sung Kang; Edwin R. Lampugnani; Jonathan Pham; Graham A. Mackay; Edward J. Newbigin; John F. Golz (Environmental Research, 2026)

Understanding Ancient Moose Populations in the Southern Rocky Mountains - William T. T. Taylor; John A. F. Wendt; Jonathan Dombrosky; Crystal C'Bearing; Mikayla Costales; Isaac A. Hart; Journey LeBeau; Adrian Johnson; Elena Lompe; Russell W. Graham; Chance Ward; Emily Lena Jones; et al. (Journal of Biogeography, 2026)
Moose ( Alces alces ) are an iconic symbol of contemporary Rocky Mountain ecosystems, and their growing abundance in Colorado and other portions of the Southern Rockies has inspired debate around their regional prehistory prior to their 20th century translocation. The Early Holocene biogeography of moose in North America is poorly characterised, due in part to their life history and logistical obstacles to their archaeozoological and biomolecular identification. Even in areas where moose are well‐established today, they are often underrepresented in archaeological assemblages. Here, we assess the premodern presence of moose in the Colorado Rockies, determining that a robust historic record for moose and poor characterisation of the archaeozoological record prior to the 19th century make it scientifically inaccurate to frame moose as ‘non‐native’ within the context of contemporary management. Location Rocky Mountains, North America. Time Period Holocene (12,000 BP—present). Taxon Alces alces . Methods We conducted a review of moose sightings in historical archives (newspapers, photos, journals, and other written accounts), ethnohistoric sources (stories, songs, oral traditions), and identifications of moose in published archaeozoological assemblages from Colorado and the Southern Rockies. Results Findings reveal a clear record for premodern moose presence in the Southern Rockies stretching back to the earliest reliable written accounts, including regular presence of female and juvenile moose, pointing to local reproduction. Archaeological assemblages include a number of premodern moose identifications dating back to the Early Holocene, corroborated by the widespread reference to moose in ethnohistoric sources from Native nations in the Southern Rockies. Main Conclusions Historical and ancient data demonstrate that moose have a deep history as part of the faunal communities of the Southern Rockies, including Colorado. As rising moose populations change contemporary wildlife management choices, decision‐makers should include careful assessment of cultural and paleoecological datasets and interdisciplinary partnerships to help build effective and accurate management plans for public and private lands.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Postglacial effusive activity at Mt Ruapehu, Aotearoa New Zealand: Lava flow volumes and eruptive rate - Pedro Doll; Ben Matthew Kennedy; Alexander Robert Lee Nichols; Jim William Cole; Dougal Bruce Townsend; Shaun Robert Eaves; Chris Edward Conway; Graham Sloan Leonard; Jonathan Davidson (Journal of Volcanology and Geothermal Research, 2025)

Biotic Mechanisms Strengthen Functional and Phylogenetic Convergence of Reef Fish Assemblages at Higher Latitudes - Nestor E. Bosch; Rick D. Stuart‐Smith; Katie May Laumann; Graham J. Edgar; Conor Waldock; J. Emmett Duffy; Jonathan S. Lefcheck (Journal of Biogeography, 2025)
Aim How communities of organisms come together has long fascinated scientists, with renewed interest in using functional and evolutionary patterns to infer mechanisms of community assembly. Ecological theory predicts that biotic interactions could lead to either divergence in the event of niche partitioning or convergence through the exclusion of competitively inferior species, but most macroecological studies attribute the latter to environmental influences. Here, we investigated the relative importance of these two opposing mechanisms across broad spatial gradients. We hypothesised stronger signals of: ( i ) convergence at high latitude owing to ecological generalism and ( ii ) divergence at low latitudes owing to specialisation. Major Taxa Studied Reef‐associated bony fishes. Location Global. Time Period 2006–2019. Methods We used a global dataset on marine reef fish assemblages comprising 2476 species at 3325 sites to disentangle the biotic drivers of community assembly across > 100° of latitude. We then applied a framework to remove environmental influences before examining whether any signs of biotic interactions remained in the trait and phylogenetic diversity of local communities relative to the (environmentally constrained) regional species pool, drawing on six functional traits and a phylogeny of bony fishes. Results Local fish assemblages were more functionally and phylogenetically similar to each other than expected based on the regional species pool at higher latitude reefs (i.e., show greater convergence). This pattern was evident after accounting for major sources of local environmental variation, suggesting exclusion of weak competitors. Functional convergence was mainly driven by traits related to resource acquisition, with high‐latitude assemblages converging towards more energetic carnivorous and planktivorous diets. Main Conclusions Our results suggest that biotic interactions drive greater trait and phylogenetic convergence from tropical to temperate zones. Likely mechanisms include increasing generalism and overlap in ecological strategies towards the poles, leading to the exclusion of weak competitors.

Reduction of postharvest fungal spoilage of tomato fruit using bacterial antagonists - Hailey R. Graham; Jonathan Ononiwu; Sydney Massine; Jason Lafontaine; Tyler J. Avis (Journal of Plant Pathology, 2025)

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Future climate projections in the global coastal ocean - Jason Holt; Anna Katavouta; Joanne Hopkins; Laurent O. Amoudry; Christian M. Appendini; Lars Arneborg; Alex Arnold; Yuri Artioli; Jerome Aucan; Barbara Berx; Laura Cagigal; Michela De Dominicis; et al. (Progress in Oceanography, 2025)

Remote sensing of electron precipitation mechanisms enabled by ELFIN mission operations and ADCS - Ethan Tsai; Akhil Palla; Austin Norris; James King; Cindy Russell; Sophie Ye; Jiashu Wu; Jason Mao; Sharvani Jha; Chanel Young; Graham Wing; Kevin Lian; et al. (Advances in Space Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Defoliation and demography interact to affect oak survival in Southern New England - Audrey Barker Plotkin; Brian Keevan; Meghan Graham MacLean; Grace Shiffrin; Jonathan R. Thompson (Forest Ecology and Management, 2025)

Synchrony and Tail‐Dependent Synchrony Have Different Effects on Stability of Terrestrial and Freshwater Communities - Shyamolina Ghosh; Blake Matthews; Sarah R. Supp; Roel van Klink; Francesco Pomati; James A. Rusak; Imran Khaliq; Niklaus E. Zimmermann; Thomas Wohlgemuth; Ole Seehausen; Christian Rixen; Martin M. Gossner; et al. (Global Ecology and Biogeography, 2025)
Aim Global change can impact the stability of biological communities by affecting species richness and synchrony. While most studies focus on terrestrial ecosystems, our research includes both terrestrial and aquatic realms. Previous works measure overall community synchrony as co‐variation among co‐occurring species, ignoring the tail dependence—when species fluctuate together at extreme abundance levels. We used community time‐series data to test two hypotheses across realms: a positive relationship between diversity (richness) and stability, and a negative relationship between synchrony and stability. Additionally, we explored how tail‐dependent synchrony contributes to variations in community stability. Location Global. Time Period 1923–2020. Major Taxa Studied 7 taxa across freshwater (fish, plants, invertebrates) and terrestrial (birds, plants, invertebrates, mammals) realms. Methods We synthesised 20+ years of species abundance/biomass data from 2668 communities across seven taxonomic groups. Using a variance‐ratio approach and copula models, we measured overall and tail‐dependent synchrony. Hierarchical linear mixed‐effects models in a Bayesian framework were used to assess the effects of richness and both synchrony types on stability. Results We found a positive diversity–stability relationship in terrestrial but not in freshwater communities, with terrestrial stability being nearly three times higher. A negative synchrony –stability relationship was found in both realms. The best model explaining stability included realm differences, richness and both types of synchronies. For freshwater, only overall synchrony significantly impacted stability, while richness and both synchrony types were key predictors for terrestrial stability. Notably, the model overestimates terrestrial stability when tail‐dependent synchrony is excluded. Main Conclusions Richness strongly enhanced terrestrial stability, offering the most extensive support for this relationship to date. In addition, tail‐dependent synchrony provides key insights into stability differences across ecosystems. As extreme environmental events increase, incorporating tail‐dependent synchrony in future stability studies is crucial.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Balancing boat‐electrofishing sampling effort against costs for nearshore fish communities in the Toronto waterfront, Lake Ontario - Sebastian Theis; Angela Wallace; Brian Graham; Brynn Coey; Lyndsay Cartwright; Mark Poesch; Rick Portiss; Jonathan L. W. Ruppert (Fisheries Management and Ecology, 2025)
To enhance management of aquatic systems, long‐term monitoring programs are crucial. However, managers often lack sufficient guidance in decision‐making. In this study, we analyzed nearshore electrofishing data from Lake Ontario spanning 18 years and over 100,000 caught fish to assess sampling designs for various coastal habitats. Using simulation, we evaluated precision of catch per unit effort (CPUE) for all species, piscivores, and specialist species, at different levels of electrofishing sampling effort. For overall CPUE in any habitat type, increased precision declined with additional electrofishing runs, particularly after reaching 30–40 runs. Adjustments in sampling effort, such as adding 10 runs per year for open‐coast sites, increased precision of overall CPUE by 10%. Adding 8 runs per year for wetlands increased precision of specialist‐species CPUE by 10%. However, additional runs in embayments did not increase precision for all species, piscivores, or specialist species. Our findings underscore the importance of considering community composition and abundance when evaluating CPUE precision and illustrates a flexible approach to optimize sampling effort in aquatic monitoring programs.

Correction: Seasonal forecasting of the European North-West shelf seas: limits of winter and summer sea surface temperature predictability - Jamie R. C. Atkins; Jonathan Tinker; Jennifer A. Graham; Adam A. Scaife; Paul R. Halloran (Climate Dynamics, 2025)

Practical non-stationary extreme value analysis of peaks over threshold using the generalised Pareto distribution: Estimating uncertainties in return values - Stan Tendijck; David Randell; Graham Feld; Philip Jonathan (Ocean Engineering, 2024)

Seasonal forecasting of the European North-West shelf seas: limits of winter and summer sea surface temperature predictability - Jamie R. C. Atkins; Jonathan Tinker; Jennifer A. Graham; Adam A. Scaife; Paul R. Halloran (Climate Dynamics, 2024)
The European North-West shelf seas (NWS) support economic interests and provide environmental services to adjacent countries. Expansion of offshore activities, such as renewable energy infrastructure, aquaculture, and growth of international shipping, will place increasingly complex demands on the marine environment over the coming decades. Skilful forecasting of NWS properties on seasonal timescales will help to effectively manage these activities. Here we quantify the skill of an operational large-ensemble ocean-atmosphere coupled global forecasting system (GloSea), as well as benchmark persistence forecasts, for predictions of NWS sea surface temperature (SST) at 2–4 months lead time in winter and summer. We identify sources of and limits to SST predictability, considering what additional skill may be available in the future. We find that GloSea NWS SST skill is generally high in winter and low in summer. GloSea outperforms simple persistence forecasts by adding information about atmospheric variability, but only to a modest extent as persistence of anomalies in the initial conditions contributes substantially to predictability. Where persistence is low – for example in seasonally stratified regions – GloSea forecasts show lower skill. GloSea skill can be degraded by model deficiencies in the relatively coarse global ocean component, which lacks dynamic tides and subsequently fails to robustly represent local circulation and mixing. However, “atmospheric mode matched” tests show potential for improving prediction skill of currently low performing regions if atmospheric circulation forecasts can be improved. This underlines the importance of coupled atmosphere-ocean model development for NWS seasonal forecasting applications.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Differences in neuroinflammation in people who started antiretroviral treatment during primary versus chronic HIV infection: an 18kDa Translocator protein (TSPO) positron emission tomography (PET) study - Jasmini Alagaratnam; John P. Thornhill; Zhen Fan; Jaime H. Vera; Jonathan Underwood; Rebecca Hall; Graham Searle; David Owen; Paul Edison; Sarah Fidler; Alan Winston (Journal of NeuroVirology, 2024)
Persistent inflammation is described in people with HIV (PWH) on antiretroviral treatment (ART). Early ART initiation is associated with reduced inflammation. We aimed to evaluate neuroinflammation, using translocator protein (TSPO) [ 11 C]PBR28 PET neuroimaging in PWH who initiated ART during acute HIV (aPWH) versus chronic HIV infection (cPWH) versus a control population. This was a cross-sectional, observational study. All participants underwent [ 11 C]PBR28 PET-CT neuroimaging. Using a two-tissue compartment model, total volume of distribution (V T ) and distribution volume ratios (DVR) using cortical grey matter as a pseudo-reference region at 20 regions of interest (ROIs) were calculated. Differences in V T and DVR were compared between groups using the Kruskall-Wallis test. Seventeen neuro-asymptomatic male PWH on ART (9 aPWH, 8 cPWH) and 8 male control participants (CPs) were included. Median (interquartile range, IQR) age was 40 (30, 46), 44 (41, 47) and 21 (20, 25) years in aPWH, cPWH and CPs, respectively. Median (IQR) CD4 (cells/µL) and CD4:CD8 were 687 (652, 1014) and 1.37 (1.24, 1.42), and 700 (500, 720) and 0.67 (0.64, 0.82) in aPWH and cPWH, respectively. Overall, no significant difference in V T and DVR were observed between the three groups at any ROIs. cPWH demonstrated a trend towards higher mean V T compared with aPWH and CPs at most ROIs. No significant differences in neuroinflammation, using [ 11 C]PBR28 binding as a proxy, were identified between cPWH, aPWH and CPs. A trend towards lower absolute [ 11 C]PBR28 binding was seen amongst aPWH and CPs, suggesting early ART may mitigate neuroinflammation.

Hurricanes pose a substantial risk to New England forest carbon stocks - Shersingh Joseph Tumber‐Dávila; Taylor Lucey; Emery R. Boose; Danelle Laflower; Agustín León‐Sáenz; Barry T. Wilson; Meghan Graham MacLean; Jonathan R. Thompson (Global Change Biology, 2024)
Nature‐based climate solutions (NCS) are championed as a primary tool to mitigate climate change, especially in forested regions capable of storing and sequestering vast amounts of carbon. New England is one of the most heavily forested regions in the United States (>75% forested by land area), and forest carbon is a significant component of climate mitigation policies. Large infrequent disturbances, such as hurricanes, are a major source of uncertainty and risk for policies relying on forest carbon for climate mitigation, especially as climate change is projected to alter the intensity and extent of hurricanes. To date, most research into disturbance impacts on forest carbon stocks has focused on fire. Here, we show that a single hurricane in the region can down between 121 and 250 MMTCO 2 e or 4.6%–9.4% of the total aboveground forest carbon, much greater than the carbon sequestered annually by New England's forests (16 MMTCO 2 e year −1 ). However, emissions from hurricanes are not instantaneous; it takes approximately 19 years for downed carbon to become a net emission and 100 years for 90% of the downed carbon to be emitted. Reconstructing hurricanes with the HURRECON and EXPOS models across a range of historical and projected wind speeds, we find that an 8% and 16% increase in hurricane wind speeds leads to a 10.7‐ and 24.8‐fold increase in the extent of high‐severity damaged areas (widespread tree mortality). Increased wind speed also leads to unprecedented geographical shifts in damage, both inland and northward, into heavily forested regions traditionally less affected by hurricanes. Given that a single hurricane can emit the equivalent of 10+ years of carbon sequestered by forests in New England, the status of these forests as a durable carbon sink is uncertain. Understanding the risks to forest carbon stocks from disturbances is necessary for decision‐makers relying on forests as a NCS.

The threat of groundwater pollution for petrifying springs; defining nutrient threshold values for an endangered bryophyte dominated habitat - Hans de Mars; Gijs van Dijk; Bas van der Weijden; Ab P. Grootjans; Lesław Wołejko; Gareth Farr; Jonathan Graham; Patrik Oosterlynck; Alfons J.P. Smolders (Environmental Pollution, 2024)

Freshwater eDNA reveals dramatic biological shifts linked to deforestation of New Zealand - Jonathan M. Waters; Steven Ni; Graham A. McCulloch (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The potential role of biofilms in promoting fouling formation in radioactive discharge pipelines - Franky Barton; Ben F. Spencer; Romain Tartèse; James Graham; Samuel Shaw; Katherine Morris; Jonathan R. Lloyd (Biofouling, 2023)

ebony underpins Batesian mimicry in melanic stoneflies - Brodie J. Foster; Graham A. McCulloch; Yasmin Foster; Gracie C. Kroos; Tania M. King; Jonathan M. Waters (Molecular Ecology, 2023)
The evolution of Batesian mimicry – whereby harmless species avoid predation through their resemblance to harmful species – has long intrigued biologists. In rare cases, Batesian mimicry is linked to intraspecific colour variation, in which only some individuals within a population resemble a noxious ‘model’. Here, we assess intraspecific colour variation within a widespread New Zealand stonefly, wherein highly melanized individuals of Zelandoperla closely resemble a chemically defended aposematic stonefly, Austroperla cyrene . We assess convergence in the colour pattern of these two species, compare their relative palatability to predators, and use genome‐wide association mapping to assess the genetic basis of this resemblance. Our analysis reveals that melanized Zelandoperla overlap significantly with Austroperla in colour space but are significantly more palatable to predators, implying that they are indeed Batesian mimics. Analysis of 194,773 genome‐wide SNPs reveals an outlier locus ( ebony ) strongly differentiating melanic versus non‐melanic Zelandoperla . Genotyping of 338 specimens from a single Zelandoperla population indicates that ebony explains nearly 70% of the observed variance in melanism. As ebony has a well‐documented role in insect melanin biosynthesis, our findings indicate this locus has a conserved function across deeply divergent hexapod lineages. Distributional records suggest a link between the occurrence of melanic Zelandoperla and the forested ecosystems where the model Austroperla is abundant, suggesting the potential for adaptive shifts in this system underpinned by environmental change.

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

On the relevance of animal behavior to the management and conservation of fishes and fisheries - Steven J. Cooke; Heather L. Auld; Kim Birnie-Gauvin; Chris K. Elvidge; Morgan L. Piczak; William M. Twardek; Graham D. Raby; Jacob W. Brownscombe; Jonathan D. Midwood; Robert J. Lennox; Christine Madliger; Alexander D. M. Wilson; et al. (Environmental Biology of Fishes, 2023)

Estimation of associated values from conditional extreme value models - Ross Towe; David Randell; Jennifer Kensler; Graham Feld; Philip Jonathan (Ocean Engineering, 2023)

Rapid adaptation in a fast‐changing world: Emerging insights from insect genomics - Graham A. McCulloch; Jonathan M. Waters (Global Change Biology, 2023)
Many researchers have questioned the ability of biota to adapt to rapid anthropogenic environmental shifts. Here, we synthesize emerging genomic evidence for rapid insect evolution in response to human pressure. These new data reveal diverse genomic mechanisms (single locus, polygenic, structural shifts; introgression) underpinning rapid adaptive responses to a variety of anthropogenic selective pressures. While the effects of some human impacts (e.g. pollution; pesticides) have been previously documented, here we highlight startling new evidence for rapid evolutionary responses to additional anthropogenic processes such as deforestation. These recent findings indicate that diverse insect assemblages can indeed respond dynamically to major anthropogenic evolutionary challenges. Our synthesis also emphasizes the critical roles of genomic architecture, standing variation and gene flow in maintaining future adaptive potential. Broadly, it is clear that genomic approaches are essential for predicting, monitoring and responding to ongoing anthropogenic biodiversity shifts in a fast‐changing world.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Mainstreaming the humanities in conservation - George Holmes; Jonathan Carruthers‐Jones; Graham Huggan; Eveline R. de Smalen; Katie Ritson; Pavla Šimková (Conservation Biology, 2022)

Connecting to the oceans: supporting ocean literacy and public engagement - Rachel Kelly; Karen Evans; Karen Alexander; Silvana Bettiol; Stuart Corney; Coco Cullen-Knox; Christopher Cvitanovic; Kristy de Salas; Gholam Reza Emad; Liam Fullbrook; Carolina Garcia; Sierra Ison; et al. (Reviews in Fish Biology and Fisheries, 2022)

Genomic signatures of parallel alpine adaptation in recently evolved flightless insects - Graham A. McCulloch; Joseph Guhlin; Ludovic Dutoit; Thomas W. R. Harrop; Peter K. Dearden; Jonathan M. Waters (Molecular Ecology, 2021)
Natural selection along elevational gradients has potential to drive predictable adaptations across distinct lineages, but the extent of such repeated evolution remains poorly studied for many widespread alpine taxa. We present parallel genomic analyses of two recently evolved flightless alpine insect lineages to test for molecular signatures of repeated alpine adaptation. Specifically, we compare low‐elevation vs. alpine stonefly ecotypes from parallel stream populations in which flightless upland ecotypes have been independently derived. We map 67,922 polymorphic genetic markers, generated across 176 Zelandoperla fenestrata specimens from two independent alpine stream populations in New Zealand's Rock and Pillar Range, to a newly developed plecopteran reference genome. Genome‐wide scans revealed 31 regions with outlier single nucleotide polymorphisms (SNPs) differentiating lowland vs. alpine ecotypes in Lug Creek, and 37 regions with outliers differentiating ecotypes in Six Mile Creek. Of these regions, 13% (8/60) yielded outlier SNPs across both within‐stream ecotype comparisons, implying comparable genomic shifts contribute to this repeated alpine adaptation. Candidate genes closely linked to repeated outlier regions include several with documented roles in insect wing‐development (e.g., dishevelled ), suggesting that they may contribute to repeated alpine wing reduction. Additional candidate genes have been shown to influence insect fecundity (e.g., ovo ) and lifespan (e.g., Mrp4 ), implying that they might contribute to life history differentiation between upland and lowland ecotypes. Additional outlier genes have potential roles in the evolution of reproductive isolation among ecotypes ( hedgehog and Desaturase 1). These results demonstrate how replicated outlier tests across independent lineages can potentially contribute to the discovery of genes underpinning repeated adaptation.

Reinventing the wheel? Reassessing the roles of gene flow, sorting and convergence in repeated evolution - Jonathan M. Waters; Graham A. McCulloch (Molecular Ecology, 2021)
Biologists have long been intrigued by apparently predictable and repetitive evolutionary trajectories inferred across a variety of lineages and systems. In recent years, high‐throughput sequencing analyses have started to transform our understanding of such repetitive shifts. While researchers have traditionally categorized such shifts as either “convergent” or “parallel,” based on relatedness of the lineages involved, emerging genomic insights provide an opportunity to better describe the actual evolutionary mechanisms at play. A synthesis of recent genomic analyses confirms that convergence is the predominant driver of repetitive evolution among species, whereas repeated sorting of standing variation is the major driver of repeated shifts within species. However, emerging data reveal numerous notable exceptions to these expectations, with recent examples of de novo mutations underpinning convergent shifts among even very closely related lineages, while repetitive sorting processes have occurred among even deeply divergent taxa, sometimes via introgression. A number of very recent analyses have found evidence for both processes occurring on different scales within taxa. We suggest that the relative importance of convergent versus sorting processes depends on the interplay between gene flow among populations, and phylogenetic relatedness of the lineages involved.

The extent and variability of storm‐induced temperature changes in lakes measured with long‐term and high‐frequency data - Jonathan P. Doubek; Orlane Anneville; Gaël Dur; Aleksandra M. Lewandowska; Vijay P. Patil; James A. Rusak; Nico Salmaso; Christian Torsten Seltmann; Dietmar Straile; Pablo Urrutia‐Cordero; Patrick Venail; Rita Adrian; et al. (Limnology and Oceanography, 2021)
The intensity and frequency of storms are projected to increase in many regions of the world because of climate change. Storms can alter environmental conditions in many ecosystems. In lakes and reservoirs, storms can reduce epilimnetic temperatures from wind‐induced mixing with colder hypolimnetic waters, direct precipitation to the lake's surface, and watershed runoff. We analyzed 18 long‐term and high‐frequency lake datasets from 11 countries to assess the magnitude of wind‐ vs. rainstorm‐induced changes in epilimnetic temperature. We found small day‐to‐day epilimnetic temperature decreases in response to strong wind and heavy rain during stratified conditions. Day‐to‐day epilimnetic temperature decreased, on average, by 0.28°C during the strongest windstorms (storm mean daily wind speed among lakes: 6.7 ± 2.7 m s −1 , 1 SD) and by 0.15°C after the heaviest rainstorms (storm mean daily rainfall: 21.3 ± 9.0 mm). The largest decreases in epilimnetic temperature were observed ≥2 d after sustained strong wind or heavy rain (top 5 th percentile of wind and rain events for each lake) in shallow and medium‐depth lakes. The smallest decreases occurred in deep lakes. Epilimnetic temperature change from windstorms, but not rainstorms, was negatively correlated with maximum lake depth. However, even the largest storm‐induced mean epilimnetic temperature decreases were typically

Investigating Prolonged Neonatal Jaundice: A Staged Approach is Superior and Conducive to Breastfeeding - Jonathan Wayland Graham; Siba Prosad Paul; Sarah Mulholland; Steven Chi Tran; Charlotte Louise Butler; Rowan Douglas Mankiewitz; Georgia Beech (Indian Journal of Clinical Biochemistry, 2021)

Persisting in a glaciated landscape: Pleistocene microrefugia evidenced by the tree wētā Hemideina maori in central South Island, New Zealand - Keith J. King; Debbie M. Lewis; Jonathan M. Waters; Graham P. Wallis (Journal of Biogeography, 2020)
Aim Repeated cycles of Pleistocene glaciation have influenced phylogeographic structure of taxa on New Zealand's South Island. Many taxa became restricted to refugia at either end of the island during glaciation, resulting in an area of low endemicity in central South Island. This area of low endemism is typified by the so‐called beech (or biotic) gap, where the absence of Nothofagus forest (and many other plant and invertebrate taxa) has been attributed to repeated glaciation. Some taxa, however, appear to have persisted in situ in localized refugia within the biotic gap. We test these alternative hypotheses in a large flightless alpine wētā (grasshopper). Location Southern Alps, South Island, New Zealand. Taxon Hemideina maori Pictet & Saussure, 1891 (Orthoptera: Anostostomatidae). Methods We used phylogeographic analysis of mitochondrial cytochrome c oxidase I ( cox1 ) and 25 nuclear DNA (nuDNA) markers to test for Pleistocene glacial microrefugia within the current montane South Island range of Hemideina maori . Results We identified eight deeply differentiated mtDNA lineages with limited sharing of haplotypes among populations. Genetic differentiation assessed using nuDNA revealed a similar pattern, with three groups broadly corresponding to the deepest mtDNA splits. The central South Island region exhibits substantial endemic mtDNA diversity and a distinctive nuclear lineage. Main conclusions These results indicate that H. maori likely persisted in microrefugia within the biotic gap during glaciation. These deep lineages are estimated to have started diverging prior to the initiation of glaciation, up to 3 Ma. These results add to a growing number of Southern Hemisphere examples of deep phylogeographic differentiation in glaciated alpine regions compared to Europe and North America, probably reflecting less intense glaciation. We suggest that other Southern Alps species showing northern and southern clades alone are more montane than alpine, and were reliant on warmer habitat to the north and south during glacial eras. Thus, there are species‐specific responses to climatic processes, influenced by distinctive habitat requirements and physiological traits.

Geographic Variation in Life-History Traits of Black Sea Bass (Centropristis striata) During a Rapid Range Expansion - Marissa D. McMahan; Graham D. Sherwood; Jonathan H. Grabowski (Frontiers in Marine Science, 2020)

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

Field-scale variability in site conditions explain phenotypic plasticity in response to nitrogen source in Pinus radiata D. Don - Marta Gallart; Jonathan Love; Dean F. Meason; Graham Coker; Peter W. Clinton; Jianming Xue; Paula E. Jameson; Jaroslav Klápště; Matthew H. Turnbull (Plant and Soil, 2019)

Phylogenetic divergence of island biotas: Molecular dates, extinction, and “relict” lineages - Graham A. McCulloch; Jonathan M. Waters (Molecular Ecology, 2019)
Island formation is a key driver of biological evolution, and several studies have used geological ages of islands to calibrate rates of DNA change. However, many islands are home to “relict” lineages whose divergence apparently pre‐dates island age. The geologically dynamic New Zealand (NZ) archipelago sits upon the ancient, largely submerged continent Zealandia, and the origin and age of its distinctive biota have long been contentious. While some researchers have interpreted NZ's biota as equivalent to that of a post‐Oligocene island, a recent review of genetic studies identified a sizeable proportion of pre‐Oligocene “relict” lineages, concluding that much of the biota survived an incomplete drowning event. Here, we assemble comparable genetic divergence data sets for two recently formed South Pacific archipelagos (Lord Howe; Chatham Islands) and demonstrate similarly substantial proportions of relict lineages. Similar to the NZ biota, our island reviews provide surprisingly little evidence for major genetic divergence “pulses” associated with island emergence. The dominance of Quaternary divergence estimates in all three biotas may highlight the importance of rapid biological turnover and new arrivals in response to recent climatic and/or geological disturbance and change. We provide a schematic model to help account for discrepancies between expected versus observed divergence‐date distributions for island biotas, incorporating the effects of both molecular dating error and lineage extinction. We conclude that oceanic islands can represent both evolutionary “cradles” and “museums” and that the presence of apparently archaic island lineages does not preclude dispersal origins.

Genomics detects population structure within and between ocean basins in a circumpolar seabird: The white‐chinned petrel - Kalinka Rexer‐Huber; Andrew J. Veale; Paulo Catry; Yves Cherel; Ludovic Dutoit; Yasmin Foster; John C. McEwan; Graham C. Parker; Richard A. Phillips; Peter G. Ryan; Andrew J. Stanworth; Tracey van Stijn; et al. (Molecular Ecology, 2019)
The Southern Ocean represents a continuous stretch of circumpolar marine habitat, but the potential physical and ecological drivers of evolutionary genetic differentiation across this vast ecosystem remain unclear. We tested for genetic structure across the full circumpolar range of the white‐chinned petrel ( Procellaria aequinoctialis ) to unravel the potential drivers of population differentiation and test alternative population differentiation hypotheses. Following range‐wide comprehensive sampling, we applied genomic (genotyping‐by‐sequencing or GBS; 60,709 loci) and standard mitochondrial‐marker approaches (cytochrome b and first domain of control region) to quantify genetic diversity within and among island populations, test for isolation by distance, and quantify the number of genetic clusters using neutral and outlier (non‐neutral) loci. Our results supported the multi‐region hypothesis, with a range of analyses showing clear three‐region genetic population structure, split by ocean basin, within two evolutionary units. The most significant differentiation between these regions confirmed previous work distinguishing New Zealand and nominate subspecies. Although there was little evidence of structure within the island groups of the Indian or Atlantic oceans, a small set of highly‐discriminatory outlier loci could assign petrels to ocean basin and potentially to island group, though the latter needs further verification. Genomic data hold the key to revealing substantial regional genetic structure within wide‐ranging circumpolar species previously assumed to be panmictic.

Ecological gradients drive insect wing loss and speciation: The role of the alpine treeline - Graham A. McCulloch; Brodie J. Foster; Ludovic Dutoit; Travis Ingram; Eleanor Hay; Andrew J. Veale; Peter K. Dearden; Jonathan M. Waters (Molecular Ecology, 2019)
Alpine ecosystems are frequently characterized by an abundance of wing‐reduced insect species, but the drivers of this biodiversity remain poorly understood. Insect wing reduction in these environments has variously been attributed to altitude, temperature, isolation, habitat stability or decreased habitat size. We used fine‐scale ecotypic and genomic analyses, along with broad‐scale distributional analyses of ecotypes, to unravel the ecological drivers of wing reduction in the wing‐dimorphic stonefly Zelandoperla fenestrata complex. Altitudinal transects within populations revealed dramatic wing reduction over very fine spatial scales, tightly linked to the alpine treeline. Broad biogeographical analyses confirm that the treeline has a much stronger effect on these ecotype distributions than altitude per se. Molecular analyses revealed parallel genomic divergence between vestigial‐winged (high altitude) and full‐winged (low altitude) ecotypes across distinct streams. These data thus highlight the role of the alpine treeline as a key driver of rapid speciation, providing a new model for ecological diversification along exposure gradients.

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Correction to: Lessons learned in the development of sustained release penicillin drug delivery systems for the prophylactic treatment of rheumatic heart disease (RHD) - Oliver D. Montagnat; Graham R. Webster; Jürgen B. Bulitta; Cornelia Landersdorfer; Rosemary Wyber; Meru Sheel; Jonathan R. Carapetis; Ben J. Boyd (Drug Delivery and Translational Research, 2018)

Lessons learned in the development of sustained release penicillin drug delivery systems for the prophylactic treatment of rheumatic heart disease (RHD) - Oliver D. Montagnat; Graham R. Webster; Jürgen B. Bulitta; Cornelia Landersdorfer; Rosemary Wyber; Meru Sheel; Jonathan R. Carapetis; Ben J. Boyd (Drug Delivery and Translational Research, 2018)

Impact of a 2-Week Oncology Placement on Medical Students’ Perception of Cancer - Jonathan Mayes; Simon Davies; Andrew Harris; Emma Wray; Graham G. Dark (Journal of Cancer Education, 2018)

Habitat Associations of Juvenile Cod in Nearshore Waters - Jonathan H. Grabowski; Christian W. Conroy; Rachel K. Gittman; Joseph T. Kelley; Sally Sherman; Graham D. Sherwood; Gail Wippelhauser (Reviews in Fisheries Science & Aquaculture, 2018)

Archipelagic genetics in a widespread Caribbean anole - R. Graham Reynolds; Tanner R. Strickland; Jason J. Kolbe; Bryan G. Falk; Gad Perry; Liam J. Revell; Jonathan B. Losos (Journal of Biogeography, 2017)
Aim We examine the influence of fluctuating sea levels in a land‐bridge archipelago on the apportioning of intraspecific genetic diversity and divergence in the widespread Puerto Rican crested anole ( Anolis cristatellus ). We compare three alternative scenarios for genetic diversification in an archipelagic species that contrast the relative influences of periodic isolation versus island connectedness driven by fluctuating sea levels. Our approach combines information from geography and population genetics to assess the influence of island size, island isolation, island historical geography, and population genetic processes such as drift on the contemporary distribution of genetic variation within and among islands. Location The Puerto Rico Bank in the Caribbean focusing primarily on the Spanish, British and U.S. Virgin Islands. Methods We used nuclear and mitochondrial DNA sequences and microsatellite genotypes sampled from A. cristatellus populations to investigate: (1) the broad‐scale pattern of phylogeographical divergence across Puerto Rico Bank islands and (2) diversification within the Virgin Islands archipelago. For the first component, we used sequence data to reconstruct the relationships among 542 samples from across the species range. For the second component, we examined the relative influences of island size, isolation, and population genetic processes on the distribution of genetic diversity across the Virgin Islands. Results In the Virgin Islands, A. cristatellus is represented by a monophyletic clade except on the island of Vieques, where two divergent clades coexist. We found evidence for non‐equilibrium dynamics in the Virgin Islands, suggesting spatial population expansion during intraglacial periods of low sea level. Main conclusions We found limited evidence that periods of island isolation affected patterns of genetic diversity and differentiation. Instead, we found that the patterns of genetic diversity and divergence in A. cristatellus in the Virgin Islands archipelago are likely shaped by long‐term persistence in the region and periods of population spatial expansion.

Exposure to predators reduces collective foraging aggressiveness and eliminates its relationship with colony personality composition - Colin M. Wright; James L. L. Lichtenstein; Graham A. Montgomery; Lauren P. Luscuskie; Noa Pinter-Wollman; Jonathan N. Pruitt (Behavioral Ecology and Sociobiology, 2017)

An Alternative Method to Niskin Sampling for Molecular Analysis of the Marine Environment - Jonathan Teague; Thomas Scott; Sanjay Sharma; George Graham; Michael Allen (Journal of Marine Science and Engineering, 2017)
The development of low-cost, open-source Remotely Operated Vehicle (ROV) systems has provided almost unrestricted access for researchers looking to monitor the marine environment in ever greater resolution. Sampling microbial communities from the marine environment, however, still usually relies on Niskin-bottle sampling (ROV or Conductivity-Temperature-Depth sampler (CTD) based), a method which introduces an inaccuracy and variability that is incompatible with metatranscriptomic analysis, for example. Here, we describe a versatile, easily-replicated platform which achieves in situ mRNA preservation, via the addition of RNAlater to filtered microbial cells, to enhance ROV or CTD functionality.

Solubility of Tin in Aqueous Media: Implications for Regulatory Ecotoxicity Testing? - Iain Wilson; Adam Peters; Graham Merrington; Jeremy Pearce; Jonathan Rickwood; Paul Cusack; Kay Nimmo (Bulletin of Environmental Contamination and Toxicology, 2017)

Multiple sulphur and lead sources recorded in hydrothermal exhalites associated with the Lemarchant volcanogenic massive sulphide deposit, central Newfoundland, Canada - Stefanie Lode; Stephen J. Piercey; Graham D. Layne; Glenn Piercey; Jonathan Cloutier (Mineralium Deposita, 2017)

Does wing size shape insect biogeography? Evidence from a diverse regional stonefly assemblage - Graham A. McCulloch; Graham P. Wallis; Jonathan M. Waters (Global Ecology and Biogeography, 2017)
Aim Dispersal ability has traditionally been seen as a key influence on species distributions, but recent biogeographical analyses have cast doubt on the strength of this association. Here we present biogeographical evidence from New Zealand's entire plecopteran fauna (100 species) to test for associations between flight ability and species range, and to determine the extent of wing reduction that is required to influence biogeographical patterns. Location The main islands of New Zealand, representing a land area of 270,000 km 2 . These islands host a diverse assemblage of endemic stoneflies, including a substantial number of wing‐reduced taxa. Methods We analyse biogeographical data, encompassing over 7000 species/locality records, across all 100 stonefly taxa recorded from New Zealand's mainland. Distributional data are analysed together with morphological data, in a phylogenetic framework, to test the hypothesis that wing length (dispersal ability) has a significant association with range size. Results Our analyses indicate a strong relationship between species wing length and area of occupancy, unconfounded by phylogenetic relationships. A significant positive correlation was also observed between geographical range and relative wing length in both sexes, with consistent patterns observed in distinct families. When the analysis was confined only to macropterous species the relationship between wing length and area of occupancy remained significant. Main conclusions This study shows that rapid switches in dispersal ability are linked to dramatic biogeographical contrasts. While complete wing loss is associated with major range reduction, it is also clear that even small reductions in wing size can significantly influence biogeographical patterns. Broadly, the analysis demonstrates that by focusing on a major regional assemblage of ecologically, and phylogenetically, similar taxa, it is possible to show that even subtle morphological shifts can be correlated with substantial biogeographical change.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Within‐river genetic connectivity patterns reflect contrasting geomorphology - Jonathan M. Waters; Dave Craw; Christopher P. Burridge; Martyn Kennedy; Tania M. King; Graham P. Wallis (Journal of Biogeography, 2015)
Aim To test the hypothesis that geomorphological features, shaped by underlying geology, can influence within‐river connectivity patterns in freshwater‐limited fishes. Location Rivers draining the eastern flanks of the Southern Alps in South Island, New Zealand. Methods We analyse up to 1624 bp of mt DNA from 499 ‘flathead’ Galaxias specimens from 145 localities across 14 different river systems. Variation among sampling sites within systems is characterized using ϕ statistics. Results Although similar levels of DNA sequence variation were detected in all rivers sampled, spatial partitioning of this variation was significantly greater within schist ( n = 5; mean ϕ ST = 0.696) than within greywacke ( n = 10; mean ϕ ST = 0.268) rivers. Main conclusions Population connectivity can be strongly influenced by underlying geology, leading to profound differences in the connectivity, phylogeography and diversity of riverine species.

Oral and inhaled p38 MAPK inhibitors: effects on inhaled LPS challenge in healthy subjects - Dave Singh; Leonard Siew; Jared Christensen; Jonathan Plumb; Graham W. Clarke; Steve Greenaway; Christelle Perros-Huguet; Nick Clarke; Iain Kilty; Lisa Tan (European Journal of Clinical Pharmacology, 2015)

Measuring individuality in habitat use across complex landscapes: approaches, constraints, and implications for assessing resource specialization - F. Joel Fodrie; Lauren A. Yeager; Jonathan H. Grabowski; Craig A. Layman; Graham D. Sherwood; Matthew D. Kenworthy (Oecologia, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

On wave radar measurement - Kevin Ewans; Graham Feld; Philip Jonathan (Ocean Dynamics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

A global alliance declaring war on cassava viruses in Africa - James Legg; Eklou Attiogbevi Somado; Ian Barker; Larry Beach; Hernan Ceballos; Willmer Cuellar; Warid Elkhoury; Dan Gerling; Jan Helsen; Clair Hershey; Andy Jarvis; Peter Kulakow; et al. (Food Security, 2014)

Aquatic Macrophytes Alter Metabolism and Nutrient Cycling in Lowland Streams - Jonathan M. O’Brien; Joanna L. Lessard; David Plew; S. Elizabeth Graham; Angus R. McIntosh (Ecosystems, 2014)

Biodiversity Offsets and the Challenge of Achieving No Net Loss - TOBY A. GARDNER; AMREI VON HASE; SUSIE BROWNLIE; JONATHAN M. M. EKSTROM; JOHN D. PILGRIM; CONRAD E. SAVY; R. T. THEO STEPHENS; JO TREWEEK; GRAHAM T. USSHER; GERRI WARD; KERRY TEN KATE (Conservation Biology, 2013)
Businesses, governments, and financial institutions are increasingly adopting a policy of no net loss of biodiversity for development activities. The goal of no net loss is intended to help relieve tension between conservation and development by enabling economic gains to be achieved without concomitant biodiversity losses. biodiversity offsets represent a necessary component of a much broader mitigation strategy for achieving no net loss following prior application of avoidance, minimization, and remediation measures. However, doubts have been raised about the appropriate use of biodiversity offsets. We examined what no net loss means as a desirable conservation outcome and reviewed the conditions that determine whether, and under what circumstances, biodiversity offsets can help achieve such a goal. We propose a conceptual framework to substitute the often ad hoc approaches evident in many biodiversity offset initiatives. The relevance of biodiversity offsets to no net loss rests on 2 fundamental premises. First, offsets are rarely adequate for achieving no net loss of biodiversity alone. Second, some development effects may be too difficult or risky, or even impossible, to offset. To help to deliver no net loss through biodiversity offsets, biodiversity gains must be comparable to losses, be in addition to conservation gains that may have occurred in absence of the offset, and be lasting and protected from risk of failure. Adherence to these conditions requires consideration of the wider landscape context of development and offset activities, timing of offset delivery, measurement of biodiversity, accounting procedures and rule sets used to calculate biodiversity losses and gains and guide offset design, and approaches to managing risk. Adoption of this framework will strengthen the potential for offsets to provide an ecologically defensible mechanism that can help reconcile conservation and development. Balances de Biodiversidad y el Reto de No Obtener Pérdida Neta

Protective Effects of 7,8-Dihydroxyflavone on Retinal Ganglion and RGC-5 Cells Against Excitotoxic and Oxidative Stress - Vivek K. Gupta; Yuyi You; Jonathan C. Li; Alexander Klistorner; Stuart L. Graham (Journal of Molecular Neuroscience, 2013)

High site fidelity and low site connectivity in temperate salt marsh fish populations: a stable isotope approach - Benjamin C. Green; David J. Smith; Jonathan Grey; Graham J. C. Underwood (Oecologia, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Ringing the changes: emerging roles for DASH at the kinetochore–microtubule Interface - Graham J. Buttrick; Jonathan B. A. Millar (Chromosome Research, 2011)

Water velocity preferences of Coho Salmon during the parr-smolt transformation - Shana M. Katzman; Jonathan Greathouse; Julie M. Roessig; Justin Graham; Dennis E. Cocherell; Joseph J. Cech (Environmental Biology of Fishes, 2010)

Hydrologic and biotic influences on nitrate removal in a subtropical spring‐fed river - James B. Heffernan; Matthew J. Cohen; Thomas K. Frazer; Ray G. Thomas; Travis J. Rayfield; Jason Gulley; Jonathan B. Martin; Joseph J. Delfino; Wendy D. Graham (Limnology and Oceanography, 2010)
We use a long‐term chemical and hydrologic record in combination with longitudinal sampling and high‐frequency nitrate (NO 3 ‐ ) measurements from in situ sensors to describe temporal and spatial patterns of nitrogen (N) inputs and removal in the spring‐fed Ichetucknee River (Columbia County, Florida) and to determine the hydrological, geomorphic, and biological factors that influence those dynamics. Over a 20‐yr period of record, NO 3 ‐N removal averaged 118 kg N d ‐1 (0.77 g N m ‐2 d ‐1 ) over the upper 5 km of the Ichetucknee River. Three independent estimates of gross autotrophicNassimilation (from gross primary production, diel NO 3 ‐ variation, and standing biomass) agreed closely but accounted for less than 20% of observed N removal. Longitudinal surveys indicate negligible or negative dissolved organic nitrogen and ammonium (NH 4 + ) production, suggesting that denitrification is the predominant mechanism of N removal in this river. A positive relationship between discharge and the magnitude of NO 3 ‐N removal shows that interactions with the surrounding floodplain exert considerable influence at high flows, and longitudinal NO 3 ‐ patterns indicate that N removal may be influenced by channel morphology. These results suggest a greater role for dissimilatory processes and hydrologic connectivity with hyporheic and floodplain sediments than has been previously recognized in highly productive spring‐fed rivers of north Florida. While hydrologic variation is the primary determinant of variation in NO 3 ‐ removal within the Ichetucknee River, comparison across systems indicates that biotic characteristics can cause significant deviation from predictions based on purely physical models of relationships between river size and N removal.

Do insects lose flight before they lose their wings? Population genetic structure in subalpine stoneflies - GRAHAM A. McCULLOCH; GRAHAM P. WALLIS; JONATHAN M. WATERS (Molecular Ecology, 2009)
Wing reduction and flightlessness are common features of alpine and subalpine insects, and are typically interpreted as evolutionary adaptations to increase fecundity and promote local recruitment. Here, we assess the impact of wing reduction on dispersal in stoneflies (Plecoptera: Gripopterygidae: Zelandoperla ) in southern New Zealand. Specifically, we present comparative phylogeographic analyses (COI; H3) of strong‐flying Zelandoperla decorata (144 individuals, 63 localities) vs. the co‐distributed but weak‐flying Zelandoperla fenestrata species group (186 individuals, 81 localities). The latter group exhibits a variety of morphotypes, ranging from fully winged to completely wingless. Consistent with its capacity for strong flight‐mediated dispersal, Z . decorata exhibited no substantial phylogeographic differentiation across its broad South Island range. Conversely the weak‐flying fenestrata species group exhibited substantial genetic structure across both fine and broad geographic scales. Intriguingly, the variable degrees of wing development observed within the fenestrata species group had no apparent impact on levels of phylogeographic structure, which were high regardless of morphotype, suggesting that even fully winged specimens of this group do not fly. This finding implies that Zelandoperla flight loss occurs independently of wing loss, and might reflect underlying flight muscle reduction.

Microarray analysis of gene expression of mouse hepatocytes of different ploidy - Pin Lu; Sandrine Prost; Helen Caldwell; Jonathan D. Tugwood; Graham R. Betton; David J. Harrison (Mammalian Genome, 2007)

Genomic and structural analysis of Syn9, a cyanophage infecting marine Prochlorococcus and Synechococcus - Peter R. Weigele; Welkin H. Pope; Marisa L. Pedulla; Jennifer M. Houtz; Alexis L. Smith; James F. Conway; Jonathan King; Graham F. Hatfull; Jeffrey G. Lawrence; Roger W. Hendrix (Environmental Microbiology, 2007)
Summary Cyanobacteriophage Syn9 is a large, contractile‐tailed bacteriophage infecting the widespread, numerically dominant marine cyanobacteria of the genera Prochlorococcus and Synechococcus . Its 177 300 bp genome sequence encodes 226 putative proteins and six tRNAs. Experimental and computational analyses identified genes likely involved in virion formation, nucleotide synthesis, and DNA replication and repair. Syn9 shows significant mosaicism when compared with related cyanophages S‐PM2, P‐SSM2 and P‐SSM4, although shared genes show strong purifying selection and evidence for large population sizes relative to other phages. Related to coliphage T4 – which shares 19% of Syn9's genes – Syn9 shows evidence for different patterns of DNA replication and uses homologous proteins to assemble capsids with a different overall structure that shares topology with phage SPO1 and herpes virus. Noteworthy bacteria‐related sequences in the Syn9 genome potentially encode subunits of the photosynthetic reaction centre, electron transport proteins, three pentose pathway enzymes and two tryptophan halogenases. These genes suggest that Syn9 is well adapted to the physiology of its photosynthetic hosts and may affect the evolution of these sequences within marine cyanobacteria.

Cephalopod diversity in commercial fisheries landings of New South Wales, Australia - Jonathan D. Nottage; Ronald J. West; Steven S. Montgomery; Ken Graham (Reviews in Fish Biology and Fisheries, 2007)

Breastfeeding and risk of ovarian cancer in two prospective cohorts - Kim N. Danforth; Shelley S. Tworoger; Jonathan L. Hecht; Bernard A. Rosner; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2007)

Marine biogeographical structure in two highly dispersive gastropods: implications for trans‐Tasman dispersal - Jonathan M. Waters; Graham A. McCulloch; Janelle A. Eason (Journal of Biogeography, 2007)
Aim Recent genetic and ecological studies of marine invertebrate species with planktotrophic larvae have inferred high rates of gene flow across wide oceanic barriers. We therefore aim to test for the genetic signature of long‐distance dispersal in two widespread and abundant marine gastropod taxa. Location The intertidal and shallow subtidal zones of southern Australia and New Zealand (NZ), which house similar marine invertebrate assemblages despite being separated by the 2000‐km‐wide Tasman Sea. Methods We used mtDNA cytochrome oxidase I gene sequence analysis of two gastropod genera exhibiting trans‐Tasman distributions, namely Austrolittorina (Littorinidae) (139 specimens; 28 localities) and Scutus (Fissurellidae) (154 specimens; 32 localities). The cool‐temperate Australian ( A. unifasciata ; S. antipodes ) and NZ ( A. antipodum ; S. breviculus ) taxa within each genus are morphologically similar but of uncertain taxonomic status. Results The mtDNA analyses indicate major trans‐Tasman genetic discontinuities for both gastropod genera, with no evidence of recent or ongoing intercontinental gene flow. Although both Scutus and Austrolittorina show significant east–west structure within southern Australia – consistent with recent studies of regional marine phylogeography – neither taxon exhibits significant differentiation within NZ. Main conclusions Morphologically conserved but biogeographically disjunct gastropod populations may exhibit striking phylogeographic discontinuities, even when dispersal abilities appear to be high. On the basis of these data we reject recent calls for the synonymy of NZ and Australian lineages.

On the elusiveness of enemy-free space: spatial, temporal, and host-plant-related variation in parasitoid attack rates on three gallmakers of goldenrods - Stephen B. Heard; John O. Stireman; John D. Nason; Graham H. Cox; Christopher R. Kolacz; Jonathan M. Brown (Oecologia, 2006)

Genetic diversity in New Zealand Galaxias vulgaris sensu lato (Teleostei: Osmeriformes: Galaxiidae): a test of a biogeographic hypothesis - Graham P. Wallis; Karen F. Judge; Julie Bland; Jonathan M. Waters; Tim M. Berra (Journal of Biogeography, 2001)
Aim To test whether a geologically recent region with low endemism shows low genetic diversity in a freshwater fish species complex, in contrast to an adjacent area with high diversity. The low endemism is generally postulated to be the combined effect of Pleistocene glaciations and the unstable nature of the recent gravel outwash from young mountains to the west. This rock aggradation has formed a plain, crossed by several braided rivers. The faunas of these rivers have the potential to interchange through flooding or course changes. Location Southern and central South Island, New Zealand (NZ). We define the boundary of these two biogeographical regions as the Waitaki River, the most southerly braided river. To the north lies the Canterbury Plain, formed from coalesced alluvial fans; to the south is the Otago peneplain and associated mountain ranges. Methods Previous work has revealed considerable genetic structuring in the stream‐resident fish Galaxias vulgaris Stokell sensu lato , including a species complex in the southern region of South Island, NZ. Using isozyme electrophoresis, we have now examined genetic variation among a total of 58 samples of non‐migratory river galaxias from 24 river systems in South Island: 16 in the central region and eight to the south. Results Whereas samples from the central region do exhibit significant genetic structuring (Wright’s F ST =0.331), they are more genetically homogeneous (mean Nei’s D = 0.032) than populations to the south of the Waitaki River ( F ST =0.826, mean D =0.374). Main conclusions The results concur with our expectations of differences between the central and southern regions. We suggest that the divergence in the south reflects geological stability, whereas relatively shallow divergences within the central region reflects the more recent formation of the Canterbury Plain and its unstable braided rivers. The genetic structuring of this group has been promoted by the absence of the marine juvenile phase that is found in five other members of the genus native to NZ. This diversity of the southern region mirrors its diverse flora and invertebrate fauna, and has conservation implications that parallel those resulting from our improved knowledge of the NZ herpetofauna through the application of genetic analysis.

Biogeography of a southern hemisphere freshwater fish: how important is marine dispersal? - Jonathan M. Waters; Lucette H. Dijkstra; Graham P. Wallis (Molecular Ecology, 2000)
Galaxias maculatus is one of the world’s most widely distributed freshwater fish. This species has a marine‐tolerant juvenile phase, and a geographical range extending through much of the southern hemisphere. We conducted phylogeographic analyses of 163 control region haplotypes of G. maculatus , including samples from New Zealand (five locations), Tasmania (one location) and Chile (one location). A lack of genetic structure among New Zealand samples suggests that marine dispersal facilitates considerable gene flow on an intra‐continental scale. The discovery of a Tasmanian‐like haplotype in one of 144 New Zealand samples indicates that inter‐continental marine dispersal occurs but is insufficient to prevent mitochondrial DNA differentiation among continents. The sister relationship of Tasmanian and New Zealand clades implies that marine dispersal is an important biogeographical mechanism for this species. However, a vicariant role in the divergence of eastern and western Pacific G. maculatus cannot be rejected.

Across the Southern Alps by river capture? Freshwater fish phylogeography in South Island, New Zealand - Jonathan M. Waters; Graham P. Wallis (Molecular Ecology, 2000)
We used DNA analysis of galaxiid fish to test a hypothesis of localized headwater capture in South Island, New Zealand. The restricted western, but widespread eastern, distributions of three nonmigratory freshwater fish species suggest that part of the east‐flowing Waiau River has been captured by the west‐flowing Buller River. However, mitochondrial control region (Kimura 2‐parameter distance = 4.1–5.4%) and microsatellite flanking sequences do not support a relationship between Waiau ( N = 4 fish sequences) and western populations ( N = 8) of Galaxias vulgaris . Instead, the point of capture is probably to the north‐east, perhaps the Nelson lakes region. Phylogenetic analysis indicates that western populations, along with populations in the north‐east ( N = 18), represent a previously unidentified monophyletic Evolutionarily Significant Unit, possibly a cryptic species. We suggest a general caveat for zoogeographic conclusions based on distributional data alone.

Characterization of microsatellite loci from a New Zealand freshwater fish ( Galaxias vulgaris ) and their potential for analysis of hybridization in Galaxiidae - Jonathan M. Waters; Yuzine B. Esa; Graham P. Wallis (Molecular Ecology, 1999)

Binding of ovarian cancer cells to immobilized hyaluronic acid - Jonathan B Catterall; Michael J Gardner; Lindsay M.H Jones; Graham A Turner (Glycoconjugate Journal, 1997)

Binding of ovarian cancer cells to immobilized hyaluronic acid - Jonathan B Catterall; Michael J Gardner; Lindsay M.H Jones; Graham A Turner (Glycoconjugate Journal, 1997)

CD44 in inflammation and metastasis - Jayne Lesley; Robert Hyman; Nicole English; Jonathan B Catterall; Graham A Turner (Glycoconjugate Journal, 1997)